2019
DOI: 10.1080/10962247.2018.1523071
|View full text |Cite
|
Sign up to set email alerts
|

Effect modification of ambient particle mortality by radon: A time series analysis in 108 U.S. cities

Abstract: Numerous studies have reported a positive association between ambient fine particles and daily mortality, but little is known about the particle properties or environmental factors that may contribute to these effects. This study assessed potential modification of radon on PM 2.5 (particulate matter with an aerodynamic diameter <2.5 μm)-associated daily mortality in 108 U.S. cities using a two-stage statistical approach. First, city-and season-specific PM 2.5 mortality risks were estimated using over-dispersed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 48 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…Another recent study also found higher PM radioactivity was associated with an elevation in both diastolic and systolic blood pressure (Nyhan et al, 2018). Blomberg et al (2018) recently found that indoor radon exposures (a source of ionizing radiation exposures), through interactions with PM, were associated with total, cardiovascular, and respiratory mortality risk based on 112 cities in the U.S. In addition to the alpha and beta emissions that accompany the decay of environmental radionucleides, gamma radiation is also frequently emitted (Stacey, 2007), indicating that PM gamma activities may be a surrogate for total radioactivity emitted from PM.…”
Section: Discussionmentioning
confidence: 91%
“…Another recent study also found higher PM radioactivity was associated with an elevation in both diastolic and systolic blood pressure (Nyhan et al, 2018). Blomberg et al (2018) recently found that indoor radon exposures (a source of ionizing radiation exposures), through interactions with PM, were associated with total, cardiovascular, and respiratory mortality risk based on 112 cities in the U.S. In addition to the alpha and beta emissions that accompany the decay of environmental radionucleides, gamma radiation is also frequently emitted (Stacey, 2007), indicating that PM gamma activities may be a surrogate for total radioactivity emitted from PM.…”
Section: Discussionmentioning
confidence: 91%
“…Daily PM 2.5 values for each city were calculated using a model that standardizes daily measurements for all monitors within a city boundary and prevents missing days from one monitor from adding false variability to the daily value as previously described in Zanobetti & Schwartz, 2009 [39, 40]. Acute exposure to PM 2.5 was calculated as the mean of 24-h PM 2.5 concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Research conducted in the USA shows large differences in radon levels, with the highest concentrations in the Northeast and Upper Midwest. The highest radon concentrations were recorded in Pennsylvania (844 Bq/m 3 ), and the lowest in Florida, Louisiana and California (11.1 Bq/m 3 ) [ 25 ].…”
Section: Natural Sources Of Radonmentioning
confidence: 99%
“…Blomberg and coauthors observed higher mortality due to cardiovascular and respiratory diseases with the simultaneous occurrence of increased concentrations of PM2.5 and radon. The authors indicate that PM2.5 can act as a vector for radon, transporting it to the bronchial tree [ 25 ].…”
Section: Radon Is An Aetiological Factor In Cancer and Noncanceroumentioning
confidence: 99%